Pratiques de la recherche avec les jeunes enfants : enjeux politiques et épistémologiques - C. Carmen Draghici; Pascale Garnier (Recherches en Éducation)
Focussed on research practices with children, and not only on children, this paper proposes a reflexive glance on the issues of two empirical inquiries conducted by the authors in two researches with two - four years old children. After the presentation of the political and social stakes of children’s voice, we show the international development of studies of early childhood education and care. We underline the “guided tour” as a visual methodology, which facilitates the researchers’ reflexivity and sustain young children’s competences, especially migrant children. We analyse how they use photography as “voice” for accounting their experiences in early childhood centres and nursery schools. As the question of children’s domination by adults is unavoidable, we emphasize that research must deal with a new meaning of children – experts of their own life, as political subjects and not only as social agent.